2021
DOI: 10.3991/ijet.v16i12.19125
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of a Learner-Centered Pedagogical Approach with Flipped Pedagogy and Digital Learning Environment in Higher Education Feedback on a Cell Biology Course

Abstract: This paper aims to examine the results of a survey of 292 first-year biology students to evaluate their perception of their learning environment, as well as their ability to handle an educational innovation such as reverse pedagogy and serious gaming integrated into a hybrid learning environment. We also present the approaches and steps that allowed us to validate our statistical study. We used a methodology to validate the instrument developed; using standard parameters, the mean and the standard deviation to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 6 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…It is well established that engagement necessitates unique techniques to promote information acquisition that is connected to students' comprehension [17,18]. Scholars have argued for a strong connection between student engagement and the specific use of a MOOC video [19], a blackboard learning management system [20], course-specific learning analytics and nudging [21] and blended learning [22,23,24,25]. Given the critical nature of the reciprocal connection between engagement and learning, it's predictable that the connection has been explored across a range of elements, measurement approaches, and domains [26].…”
Section: Student Engagementmentioning
confidence: 99%
“…It is well established that engagement necessitates unique techniques to promote information acquisition that is connected to students' comprehension [17,18]. Scholars have argued for a strong connection between student engagement and the specific use of a MOOC video [19], a blackboard learning management system [20], course-specific learning analytics and nudging [21] and blended learning [22,23,24,25]. Given the critical nature of the reciprocal connection between engagement and learning, it's predictable that the connection has been explored across a range of elements, measurement approaches, and domains [26].…”
Section: Student Engagementmentioning
confidence: 99%
“…From Table 4, it can be indicated that 7.1% of the total of 756 students indicated that they totally disagreed with indicators AL4 and M4, 16.7% who agreed that the virtual classroom helped group learning by allowing communication through digital platforms (AL4) indicated that they neither agree nor disagree that the virtual classroom offers multiple advantages that it meets the expectations of the asynchronous learning process (M4). Ouchaouka et al [34] it is pointed out that the indicators of communication modalities and digital learning environments reflect an excellent internal consistency with relational values of 0.88 and 0.84 regarding the reversed pedagogy approach of the biology course. Likewise, in Table 5 we will analyze the relationship of the students' perception according to the AL5 and M2 indicators.…”
Section: Resultsmentioning
confidence: 99%
“…Classroom practice is implemented using a learner-centered approach (Ouchaouka et al, 2021;Sanjana, 2020), where students are activated to be involved in activities and produce target language utterances. The activation of students can be observed in the form of teachers' employment of interaction patterns (Ahn, 2019;Thi & Thuy, 2021) during the language teaching process.…”
Section: Literature Reviewmentioning
confidence: 99%